Analisis Perilaku Konsumen Muslim dalam Penggunaan Layanan Digital Banking Syariah: Studi Literatur - Hardyansah, Rommy; Issalillah, Fayola; Darmawan, Didit; Khayru, Rafadi Khan; Arifin, Samsul (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2024)
This study aims to analyze the effect of digital literacy and sharia literacy on the level of adoption of Islamic digital banking services and identify barriers faced by Islamic banking to meet Muslim consumer expectations of product innovation and service security. The approach used is a literature study by reviewing various scientific articles, books, and reports related to the topic. The findings show that digital literacy and sharia literacy are the main factors influencing the adoption of Islamic digital banking services. Digital literacy helps consumers understand technology, while sharia literacy improves understanding of the halalness of financial services. The combination of the two creates stronger trust in Islamic digital banking services. However, there are some significant barriers, such as the low level of digital and sharia literacy among certain communities, technological limitations in Islamic banking, and regulations that do not support innovation. In addition, consumer concerns about the security of digital services and the lack of Islamic financial education reduce consumer confidence. These barriers are exacerbated by the lack of investment in technology development and product innovation in the Islamic banking sector. This study concludes that digital and sharia literacy are essential elements to increase the adoption of Islamic digital banking services. The results of this study provide insights into the importance of overcoming these barriers to support the development of digital Islamic banking services and increase financial inclusion among Muslim consumers.